The Divinity of Christ in the Gospel of John - Pieter Verster (Pharos Journal of Theology, 2023)
It is generally accepted that the Gospel of John proclaims Jesus as Lord and God, One with the Father. There are, however, those who challenge this view. Recently, Nagel (2019) pointed out that Jesus is not regarded as Theos in the Gospel of John. He refutes the classical understanding of the texts that Jesus is One with God. He does not regard both the Logos of John 1:1-2 and the confession of Thomas in John 20:28 as references to Jesus. Theological views of Jesus in John are often understood as that he is One with God. To engage the most important texts in John, this article explores the views of theologians in the commentaries, especially Brown (1971a; 1971b), Schnackenburg (1968; 1980) and Von Wahlde (2010a; 2010b) From these commentaries and from engaging the texts, it is clear that Logos in John 1:1-2 refers to Jesus and that Thomas’ confession of Jesus as Lord and God is evidence of Jesus’ Divinity. This does not mean that Jesus is not also human, but that he should be acknowledged as human, as the Son of God, but also as God One with Father. Jesus’ reference to himself as “I am” has an implication for his Divinity, as it is related to YHWH who is called “I am” in the Old Testament. Jesus is the One who is sent from God, and those who see him also see the Father. All the evidence points to the Gospel of John as accepting Jesus as God, One with the Father and the Holy Spirit in a triune Godhead.